The Effectiveness of Using Venn Diagrams and Fishbone Technique in Enhancing the Performance Level of Grade VI Students in Edukasyon sa Pagpapakatao for the School Year 2023-2024" - Tiburcio, Cesar A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study evaluated the effectiveness of using Venn Diagrams and the Fishbone Technique in enhancing the performance level of Grade VI students in Edukasyon sa Pagpapakatao (ESP) during the school year 2023-2024. Conducted at Sto. Tomas Elementary School, Subic, Zambales, the research involved 25 Grade VI students (12 males and 13 females) as respondents. The study aimed to determine the students' performance levels before and after the implementation of these tools and to identify observable changes in their performance. Data were gathered through pre-tests, post-tests, and group activities, which were analyzed using frequency distribution, scoring rubrics, and a comparison of means and standard deviations. Results revealed that the students' performance was average before using the tools but significantly improved to an excellent level after their implementation. The Venn Diagram and Fishbone Technique facilitated deeper understanding and meaningful learning among students, confirming their effectiveness in ESP lessons. The findings highlighted the importance of systematic presentation and alignment of teaching tools with learning competencies. Further research is recommended to explore the broader applicability of these techniques in other subject areas.